Nanoconfined Chlorine-Substituted Monomethine Cyanine Dye with a Propionamide Function Based on the Thiazole Orange Scaffold—Use of a Fluorogenic Probe for Cell Staining and Nucleic Acid Visualization - Nikolay Ishkitiev; Maria Micheva; Marina Miteva; Stefaniya Gaydarova; Christo Tzachev; Vesela Lozanova; Valentin Lozanov; Diana Cheshmedzhieva; Meglena Kandinska; Sonia Ilieva; Raimundo Gargallo; Stanislav Baluschev; et al. (Molecules)
The development of fluorescence-based methods for bioassays and medical diagnostics requires the design and synthesis of specific markers to target biological microobjects. However, biomolecular recognition in real cellular systems is not always as selective as desired. A new concept for creating fluorescent biomolecular probes, utilizing a fluorogenic dye and biodegradable, biocompatible nanomaterials, is demonstrated. The synthesis of a new dicationic asymmetric monomethine cyanine dye with benzo[d]thiazolium-N-propionamide and chloroquinoline end groups is presented. The photophysical properties of the newly synthesized dye were examined through the combined application of spectroscopic and theoretical methods. The applicability of the dye as a fluorogenic nucleic acid probe was proven by UV-VIS spectroscopy and fluorescence titration. The dye–nucleic acid interaction mode was investigated by UV-Vis and CD spectroscopy. The newly synthesized dicationic dye, like other similar fluorogenic structures, limited permeability, which restricts its use as a probe for RNA and DNA. To enhance cellular delivery, we utilized a patented technology that employs solid, insoluble lipid nanoparticles. This method ensures the complete introduction of the dye into cells while minimizing activity outside the cells. In our study involving two human cell lines, we observed improved penetration through the cell membrane and distinctive selectivity in visualizing nucleic acids within the cytoplasm and nucleus.